Menemukan Moderasi Beragama dalam Kaderisasi Dakwah: Kajian pada Pemuda Persatuan Islam Jawa Barat - Aep Kusnawan; Ridwan Rustandi (NALAR, 2021)
This article aims to analyze the model of the religious moderation-based dakwah training concerning about the patterns, processes and strategies of regeneration in Pemuda Persatuan Islam, West Java. The research is focused on observing the cultivation of religious moderation values in the regeneration program such as recruitment, training, coaching and projecting the distribution of cadres. This study uses a constructivism paradigm and qualitative approach through case studies. The data was collected through observation, interviews, documentation and literature studies. The results showed that the patterns and processes of regeneration in Pemuda Persatuan Islam West Java are projected to create the da'wah resources with the qualities of being open-minded, critical, responsive, adaptive, collaborative and transformative. The strategy of cultivating the values of religious moderation is carried out in every stage of the regeneration of Pemuda Persatuan Islam West Java, both formal and informal, especially on the material side, methods, instructors, strategic issues, duration, and evaluation techniques. The research implication is expected to be able to present a dakwah training model based on religious moderation in da'wah organizations in West Java.Keyword: Dakwah training; Religious moderation; Regeneration Pemuda Persis